2010
DOI: 10.1177/1534735409359773
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma wenyujin Extract Induces Apoptosis and Inhibits Proliferation of Human Cervical Cancer Cells In Vitro and In Vivo

Abstract: An essential oil extract, derived from the rhizome of Curcuma wenyujin (CWE), possesses antioxidative, antimicrobial, and anti-inflammatory properties. However, it remains unknown how exactly CWE inhibits tumor growth. In this study, using human cervical cancer HeLa cells, the authors postulated that CWE has the ability to inhibit tumor growth. The study shows that CWE dose-dependently suppressed colony formation and inhibited the proliferation of HeLa cells through blockade of cell cycle progression at G1 pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 49 publications
(74 reference statements)
1
33
0
Order By: Relevance
“…Thus, signaling pathways involved in enhancing apoptosis are potential targets for identifying innovative drug candidates. There are a number of previous reports demonstrating that the oily extracts of C. wenyujin induce cellular apoptosis and inhibit proliferation in certain cancer cell lines (10,(28)(29)(30). The present study focused on curcumol, one of the active compounds isolated from the curcuma oil (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, signaling pathways involved in enhancing apoptosis are potential targets for identifying innovative drug candidates. There are a number of previous reports demonstrating that the oily extracts of C. wenyujin induce cellular apoptosis and inhibit proliferation in certain cancer cell lines (10,(28)(29)(30). The present study focused on curcumol, one of the active compounds isolated from the curcuma oil (12).…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric as a common food belonging to Curcuma longa showed anti-inflammatory, antitumor and antioxidative properties [8]. Curcuminoids, as its main active compounds, increased the accumulation of drug through the interactions at the substrate-binding sites [1].…”
Section: Introductionmentioning
confidence: 99%
“…C. wenyujin rhizome extract contains a variety of bioactive ingredients, such as curdione (Xia et al, 2012), aurantiamide (Ma et al, 2009;Xia et al, 2012), and sesquiterpene (Sun et al, 2009;Dong et al, 2013;Zhu et al, 2013a). These substances can not only induce apoptosis (Xiao et al, 2008;Lim et al, 2010), inhibit platelet aggregation (Xia et al, 2012), and tumor growth (Sun et al, 2009;Lim et al, 2010), but also serve as clinical agents of anti-oxidation, anti-microbial action (Dong et al, 2013;Zhu et al, 2013b), and anti-inflammation (Tohda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mohanty et al (2011) assessed the genetic stability of micropropagated Zingiber rubens by using RAPD and ISSR markers, and found that the duration of the culture period (more than two years) did not affect the plants' genetic integrity; Das et al (2011) determined the genetic diversity and molecular classification of nine Curcuma species from northeast India using DNA fingerprinting (ISSR, RAPD, and amplified fragment length polymorphism). However, in the case of C. wenyujin, previous studies have mainly focused on the isolation and characterization of the plant's bioactive ingredients (Xia et al, 2012;Zhu et al, 2013a), as well as their functions (Sun et al, 2009;Lim et al, 2010;Zhu et al, 2013b). Only three studies have been conducted on the genetic diversity (or variation) of C. wenyujin using single DNA markers (RAPD or ISSR) (Tao et al, 2007(Tao et al, , 2009Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%